Electropolished Titanium Implants with a Mirror-Like Surface Support Osseointegration and Bone Remodelling - Cecilia Larsson Wexell; Furqan A. Shah; Lars Ericson; Aleksandar Matic; Anders Palmquist; Peter Thomsen (Advances in Materials Science and Engineering)
This work characterises the ultrastructural composition of the interfacial tissue adjacent to electropolished, commercially pure titanium implants with and without subsequent anodisation, and it investigates whether a smooth electropolished surface can support bone formation in a manner similar to surfaces with a considerably thicker surface oxide layer. Screw-shaped implants were electropolished to remove all topographical remnants of the machining process, resulting in a thin spontaneously formed surface oxide layer and a smooth surface. Half of the implants were subsequently anodically oxidised to develop a thickened surface oxide layer and increased surface roughness. Despite substantial differences in the surface physicochemical properties, the microarchitecture and the composition of the newly formed bone were similar for both implant surfaces after 12 weeks of healing in rabbit tibia. A close spatial relationship was observed between osteocyte canaliculi and both implant surfaces. On the ultrastructural level, the merely electropolished surface showed the various stages of bone formation, for example, matrix deposition and mineralisation, entrapment of osteoblasts within the mineralised matrix, and their morphological transformation into osteocytes. The results demonstrate that titanium implants with a mirror-like surface and a thin, spontaneously formed oxide layer are able to support bone formation and remodelling.